Living on the shores of the Alboran Sea. The Neolithic on the coast of Málaga (Spain) a multiproxy approach. - Simón-Vallejo, María D.; Lozano-Francisco, María del Carmen; Riquelme-Cantal, José Antonio; Macías Tejada, Sara; Camuera, Jon; Uzquiano Ollero, Paloma; Sánchez Marco, Antonio; Garrido Anguita, Juan M.; Jiménez- Espejo, Francisco; Parrilla-Giráldez, Rubén; Vera-Lozano, José Antonio; Vera-Peláez, José Luis; et al. (Springer Nature, 2025)
Context The coast of Málaga is one of the core areas for the Neolithic in southern Iberia with the earliest occupations dating to the middle of the 8th millennium cal BP. From the outset, evidence shows a fully developed and highly diversified system of agriculture and animal husbandry. The palaeoenvironmental conditions during this period in the southern Iberian Peninsula reveal phases of aridity. Objectives This study aims to understand how Neolithic communities adapted to these adverse environmental conditions. It also explores the role of wild resources and seasonal patterns in subsistence strategies. Methods A multiproxy approach was applied, combining regional palaeoenvironmental data with archaeological, archaeofaunal, archaeobotanical and anthropological evidence. The analysis focuses on sites located near aquifer discharges. Results Fully developed and highly diversified agriculture and herding practices are documented from the earliest Neolithic phases. The challenges posed by arid conditions appear to have been mitigated by settlement in areas linked to major aquifer outlets and by the cultivation of drought-resistant cereals. Multiple lines of evidence suggest a seasonal pattern of occupation, primarily from late autumn to early summer, when marine resources were likely exploited. Neolithic groups may have engaged in regular hunting and gathering activities or maintained interactions with local Epipalaeolithic–Mesolithic populations. Agricultural and pastoral management emerge as key factors for evaluating the contribution of wild resources to their subsistence. Conclusions The integration of environmental, archaeological and biological records provides a more holistic perspective and better understanding of Neolithic economy and society along the Málaga coast between c. 7.6th—5th millennium cal BP, offering insights into subsistence strategies under arid conditions in a coastal setting.
Keywords: Neolítico; Agricultura; Ganadería; Recursos marinos; Neolithic; Agriculture; Livestock; Palaeoenvironment; Marine resources; Seasonality